2015
DOI: 10.18632/oncotarget.3361
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of decitabine in combination with G-CSF, low-dose cytarabine and aclarubicin in newly diagnosed elderly patients with acute myeloid leukemia

Abstract: PurposeThis prospective phase II, open label, study was designed to assess the efficacy and safety of D-CAG induction treatment for elderly patients with newly diagnosed AML.Experimental DesignAll patients in this study were treated with decitabine of 15 mg/m2 for 5 days and G-CSF for priming, in combination with cytarabine of 10-mg/m2 q12h for 7 days and aclarubicin of 10 mg/day for 4 days (D-CAG).ResultsAmong 85 evaluable patients, overall response rate (ORR) and complete remission (CR) were 82.4% and 64.7%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 31 publications
5
50
0
Order By: Relevance
“…The results revealed increased response rate and prolonged survival in patients treated with decitabine priming prior to low-dose chemotherapy compared with those treated with chemotherapy alone. Consistent with the results of previous clinical trials (Lee et al 2011; Li et al 2015; Song et al 2012), the median OS of patients achieving CR in the current study was significantly longer than that of patients with non-CR regardless of the treatment (decitabine priming or chemotherapy alone). A subgroup analysis in the current study showed a higher CR (65.5%) with a longer OS (22.4 months) in patients at <60 years of age in the decitabine priming group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results revealed increased response rate and prolonged survival in patients treated with decitabine priming prior to low-dose chemotherapy compared with those treated with chemotherapy alone. Consistent with the results of previous clinical trials (Lee et al 2011; Li et al 2015; Song et al 2012), the median OS of patients achieving CR in the current study was significantly longer than that of patients with non-CR regardless of the treatment (decitabine priming or chemotherapy alone). A subgroup analysis in the current study showed a higher CR (65.5%) with a longer OS (22.4 months) in patients at <60 years of age in the decitabine priming group.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study from our research group, decitabine followed by idarubicin produced synergistic anti-leukemia effects in both cultured cells and xenograft animal models (Li et al 2014). Clinical studies that examined the combination of decitabine and chemotherapeutics, such as standard DA (daunomycin and cytarabine), low-dose AA, and CAG (G-CSF and low-dose AA) suggested CR rate at 50–60% and OR rate at 60–90% in AML and MDS/AML (Li et al 2015; Scandura et al 2011; Song et al 2012). In a previous study (Ye et al 2016), we reported a CR rate of 43% in MDS, 75% in MDS/AML and 29% in relapsed/refractory AML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approval of DAC in the European Union in 2012 for the treatment of ≥65-year-old patients with AML marks the potential for hypomethylating agents in elderly AML patients. Recent studies using DAC before G-CSF, low-dose cytarabine, and aclarubicin, or before full-dose cytarabine and daunorubicin have reported encouraging results [15,16,17]. It has been shown that DAC followed by low-dose idarubicin/cytarabine (D-IA) has an increased antileukemia effect compared to traditional chemotherapy [18].…”
Section: Introductionmentioning
confidence: 99%